Political Struggle for the Aesthetics of the Urban Commons in Turkey - Tijen Tunali (User Experience & Urban Creativity)
The common features of the protests sweeping the world since 1994 are their anti-austerity stance, the denunciation of corruption, the critique of mainstream institutions and the media, and increasing social inequality in deeply segregated urban landscapes. Across the world, people of different nations, operating in highly diverse cultural, social and historical contexts, have discovered who they are as citizens and what constituent power they have in relation to their governments. Many accounts have argued that in these recent urban social movements, the protestors have had diverse identities, interests and critical capacities, and yet they have collectively engaged in an aesthetic and sensory experience and discovered it to be a valid political instrument to undermine dominant political styles, challenge authoritarian rigidity and subvert the aesthetico-political language of officialdom (Bruff 2012, Della Porta and Mattoni 2014). The creation of political spaces of experience where imagination, creativity and pleasure are embraced and celebrated as integral to political engagement in order to “permit actors to live according to their own principles, to knit different social relations and to express their subjectivity (Pleyers 2010, p. 39).” The question this paper asks is, how this relates to empowering civil society?